Kepuasan Pasien Rawat Inap: Analisis Dimensi Kualitas Pelayanan di RSUD Panembahan Senopati Bantul DIY - Mursyid; Suliantoro; Nur Rahmatullayla Tahir (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
Patient satisfaction is an important indicator for evaluating the quality of hospital services. This study aims to examine the effect of SERVQUAL dimensions on inpatient satisfaction at RSUD Panembahan Senopati Bantul. A quantitative explanatory approach was employed using data collected from 79 inpatients selected through purposive sampling. The data were analyzed using multiple linear regression. The results indicate that only the assurance and responsiveness dimensions have a significant positive effect on patient satisfaction, whereas reliability, tangibles, and empathy do not show significant effects. Nevertheless, the five SERVQUAL dimensions simultaneously influence patient satisfaction. These findings suggest that patients place greater emphasis on confidence, trust, and prompt service than on other dimensions of service quality. The findings provide practical insights for hospital management to prioritize service quality improvement strategies and enhance patient satisfaction.